Pengaruh Kemudahan Belanja Online dan Pengendalian Diri Terhadap Perilaku Konsumtif dengan Peminatan Ekonomi Sebagai Variabel Moderator - Nadia Salsabilla Burhan; Leny Noviani; Khresna Bayu Sangka (Journal on Education, 2023)
This study aims to determine the effect of (1) online shopping convenience and (2) self-control on consumptive behavior as well as knowing economic interest in moderating the effect of (3) online shopping convenience and (4) self-control on SMA Negeri 5 Surakarta students. The research design is quantitative descriptive. The population of this study was 706 consisting of class XI and XII students of SMA Negeri 5 Surakarta. The sampling technique used proportionate stratified random sampling with sample details of 63 from XII IPS, 65 from XI IPS, 63 from XII MIPA, and 65 from XI MIPA so that a sample of 256 was collected. Data collection techniques used a questionnaire. Validity test using Pearson Product Moment and reliability using Cronbach Alpha and analysis was carried out using (MRA). Through processing the research data, it was found that the ease of online shopping (0.353) and self-control (0.601) had no effect on consumptive behavior because both variables showed a Sig value > 0.05 with a coefficient of determination of 0.04%. Then it is known that the economic interest variable does not have a moderating effect on the ease of online shopping and self-control of consumptive behavior.